Wastewaters, with or without Hospital Contribution, Harbour MDR, Carbapenemase-Producing, but Not Hypervirulent Klebsiella pneumoniae - Adela Teban-Man; Anca Farkas; Andreea Baricz; Adriana Hegedus; Edina Szekeres; Marcel Pârvu; Cristian Coman (MDPI AG, 2021)
Carbapenemase-producing Klebsiella pneumoniae (CPKP) isolated from influent (I) and effluent (E) of two wastewater treatment plants, with (S1) or without (S2) hospital contribution, were investigated. The strains belonged to the Kp1 phylogroup, their highest frequency being observed in S1, followed by S2. The phenotypic and genotypic hypervirulence tests were negative for all the strains tested. At least one carbapenemase gene (CRG), belonging to the blaKPC, blaOXA-48, blaNDM and blaVIM families, was observed in 63% of CPKP, and more than half co-harboured two to four CRGs, in different combinations. Only five CRG variants were observed, regardless of wastewater type: blaKPC-2, blaNDM-1, blaNDM-6, blaVIM-2, and blaOXA-48. Sequence types ST258, ST101 and ST744 were common for both S1 and S2, while ST147, ST525 and ST2502 were found only in S1 and ST418 only in S2. The strains tested were multi-drug resistant (MDR), all being resistant to beta-lactams, cephalosporins, carbapenems, monobactams and fluoroquinolones, followed by various resistance profiles to aminoglycosides, trimethoprim-sulphamethoxazole, tigecycline, chloramphenicol and tetracycline. After principal component analysis, the isolates in S1 and S2 groups did not cluster independently, confirming that the antibiotic susceptibility patterns and gene-type profiles were both similar in the K. pneumoniae investigated, regardless of hospital contribution to the wastewater type.